THE ROLE AND IMPORTANCE OF THE POPULATION FACTOR IN SOME THEORIES OF TERRITORIAL ORGANIZATION (Scientific journal of the Fergana State University, 2024)
The article examines unique theories that emerged as a result of the development of the sciences of economic geography and regional economics, starting from the 19th century. In particular, among them the leading theories devoted to issues of territorial organization are analyzed, based on the essence of the geographical location in each organization. Of course, based on the human factor, which is considered the main reason for any organization in modern society, it is justified that the population (man) is always at the core of the organization, and that the process of organization is carried out from the worldview of a person and his interests (economic, social, environmental). The article also discusses important ideas and theories in matters of territorial organization of the population.